The educational value of using bi-lingual instructional practice in students’ Writing Skills in Entomology Course at KUE - Bekau Atnafu Taye; Angeline Mbogo Barrett (African Journal of Teacher Education)
This paper reports on small-scale action research conducted with students in the final year of their degree at Kotebe University of Education. We had identified a problem whereby students majoring in Biology tended to express their content knowledge in the form of lists rather than in coherent sentences and complete paragraphs. We consequently designed an intervention that explicitly guided the students to compose short pieces of academic writing within four scientific genres: description, comparison, components and classification. The intervention was evaluated using pre- and post-tests and a student focus group discussion involving around one third of the class. The results showed that after six weeks, all the students were able to write coherent, well-organized paragraphs using appropriate scientific language. Students attributed their improvement to the formative feedback they received throughout the six-week intervention. This small-scale study suggests that cross-curricular language support has considerable potential for developing pre-service teachers’ writing skills. However, realizing this potential requires collaboration between language and other subject teachers. We relate the findings to previous research in Tanzania, which focused on developing pre-service teachers’ pedagogic skills for supporting learners through language transition. The policy implications of using home language (in this case Amharic) as the medium of instruction in higher education institutions where English is the language of instruction should be considered for science teachers. We conclude by arguing for a joined-up approach to teacher education for multilingual education systems and suggest some priorities for further research.